Chemical Investigation of Mixed Ligand Complexes of Co(II), Ni(II), Cu(II) with Malonic Acid and Pyridine - KELKAR, V.D.; KANASE, D.G.; KADAM, S.S.; TAKALE, S.T. (Asian Journal of Chemistry, 2010)
The preparation and characterization of mixed ligand complexes of Co (II), Ni (II) and Cu (II) with malonic acid as primary ligand and pyridine as secondary ligand has been reported. The composition of complexes is confirmed by chemical analysis, AAS, TGA and electrical conductivity. The general formulae of the mixed ligand complexes, malonate complexes and pyridine complexes are [M(MO)L2], [M(MO)(H2O)4] and [M(L)2Cl2], respectively where M = Ni(II), Co(II), Cu(II); MO = C3H2O4 [malonic acid] and L = C6H5N [pyridine]. The magnetic moment values for the M(II) complexes are as per expected spin only values. The IR spectra of the complexes confirm the coordination of metal ion with ligands. The complexes seem to have possible tetrahedral geometry of mixed ligand complexes and pyridine complexes and octahedral geometry of malonate complexes.